The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00264-012-1772-6
|View full text |Cite
|
Sign up to set email alerts
|

Medial portal technique for single-bundle anatomical Anterior Cruciate Ligament (ACL) reconstruction

Abstract: The aim of the paper is to describe the medial portal technique for anatomical single-bundle anterior cruciate ligament (ACL) reconstruction. Placement of an ACL graft within the anatomical femoral and tibial attachment sites is critical to the success and clinical outcome of ACL reconstruction. Non-anatomical ACL graft placement is the most common technical error leading to recurrent instability following ACL reconstruction. ACL reconstruction has commonly been performed using a transtibial tunnel technique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 18 publications
1
76
0
5
Order By: Relevance
“…The radiographic assessment by Bernard and Hertel of the ACL position showed that the ligament was relatively high and vertical. We now drill the femoral tunnel through an anteromedial portal to achieve a lower, more horizontal and, hence, more anatomical position of the ACL [19,20]. However, the clinical relevance of this is still the subject of debate; at present, none of these procedures fully restores both kinematics and biomechanics of the knee [21].…”
Section: Discussionmentioning
confidence: 99%
“…The radiographic assessment by Bernard and Hertel of the ACL position showed that the ligament was relatively high and vertical. We now drill the femoral tunnel through an anteromedial portal to achieve a lower, more horizontal and, hence, more anatomical position of the ACL [19,20]. However, the clinical relevance of this is still the subject of debate; at present, none of these procedures fully restores both kinematics and biomechanics of the knee [21].…”
Section: Discussionmentioning
confidence: 99%
“…The femoral tunnel was prepared using the Antero-medial arthroscopy portal technique. 11 As the average graft diameter was 9mm, a 7 or 6 mm femoral tunnel offset guide was used to locate the femoral tunnel through anteromedial portal. Femoral tunnel was drilled at 2 or 10 o' clock position through this anteromedial portal over a guide wire.…”
Section: Methodsmentioning
confidence: 99%
“…There were 14 further surgeons who had abandoned the "double bundle" technique citing that they did not believe this to be a "gold standard" approach in eight responses, with four surgeons citing results being no better than single tunnel technique, one surgeon citing the fact that they perform all-inside surgical method, and one surgeon stating that they still use "double bundle" when there is a large footprint to cover, though did not give specific parameters for which they may change operative strategy. Just less than 60% of surgeons who responded use a separate incision/arthroscopy port site (as described by Brown et al [2]) to aid placement of the tunnels (n = 100) with 35% using transtibial drilling method, n = 58. Six respondents use a retrograde reaming technique to position the femoral tunnel (Arthrex FlipCutter).…”
Section: Reconstruction Architecture Tunnel Placement and Fixationmentioning
confidence: 99%